Involvement of Women in Agriculture and Livestock Activities in Arid Region of Rajasthan, India - Singh, Bhagwan; Srivastava, Soma (Annals of Arid Zone, 2018)
The present study was conducted in Ummednagar village of tehsil (Administrative unit) Mandor of Jodhpur district. The village was selected purposively under the transfer of technology program supported by CAZRI, Jodhpur. Data were collected from a sample of 50 farm women on activities related to agricultural production, livestock related activities, domestic works and role in decision making. Study revealed that there was a clear differentiation among activities performed by male and female members individually besides overlapping in few activities which they performed jointly. Regarding agricultural activities like field preparation bunding and clearing weeds, harvesting and transport of harvest, majority considered them as joint work. However in case of weeding (72.22%), threshing (52.78%) and winnowing (77.77%) females were more involved in these operations and involvement of male members was very less (16-33%). In case of livestock activities except heath care (13.88%) and marketing of produce (6.66%) women were always involved in all the other activities like fodder collection, drying, feeding, cleaning, milking, processing milk etc. Regarding different household works the contribution of women was very high (91.67-100%) except marketing for household provisions which was primarily done by the male members (58.33%) or jointly (41.66%). Regarding decision making in livestock, it is evident from the data that most of the decisions about breeding (66.66%), feeding (83.33%) as well as management of cattle were taken jointly (85.33%). In case of health parameters activities like consultation, vaccination and control of parasites were taken care by their male counterparts. In case of farm credit, investment of added profit and adoption of innovative technologies, the male counterparts dominated and participation of female members was very low or negligible.Key words: Decision making, livestock, household, agricultural activities, arid.